Biological functions and therapeutic applications of human mucosal-associated invariant T cells - Ying Fang; Yuning Chen; Shaoqiang Niu; Zibai Lyu; Yanxin Tian; Xinyuan Shen; Yan-Ruide Li; Lili Yang (2025)
Abstract Mucosal-associated invariant T (MAIT) cells are a unique subset of innate-like T lymphocytes that bridge innate and adaptive immunity. Characterized by their semi-invariant T cell receptor (TCR) and abundant localization in mucosal tissues, MAIT cells recognize microbial metabolites, primarily derived from the riboflavin biosynthesis pathway, presented by the major histocompatibility complex (MHC)-related protein 1 (MR1). This interaction, along with co-stimulatory signals, triggers rapid immune responses, including cytokine secretion and cytotoxic activity, highlighting their importance in maintaining immune homeostasis and combating infections. This review provides an in-depth overview of MAIT cell biology, including development, activation pathways, and functional diversity, highlighting their protective roles in immunity, contributions to diseases like cancer and inflammatory bowel disease (IBD), and context-dependent dual functions in health and pathology. This review also highlights the emerging therapeutic potential of MAIT cells in immunotherapy. Their unique TCR specificity, abundance, and tissue-homing properties make them ideal candidates for engineering novel therapies, such as chimeric antigen receptor (CAR)-MAIT cells, targeting infections, cancers, and autoimmune diseases. Challenges like antigen escape, T cell exhaustion, and CAR design optimization must be addressed to enhance clinical efficacy. In summary, MAIT cells are integral to immune function, and their therapeutic potential presents exciting opportunities for the treatment of a wide range of diseases. Further research is essential to unlock the full potential of these versatile immune cells.